Season Suspension and Summer Extension: Unique Opportunity for Professional Team-Sport Athletes and Support Staff During and Following the COVID-19 Crisis - Huyghe, Thomas; Bird, Stephen; Calleja-González, Julio; Alcaraz, Pedro E. (Frontiers in Sports and Active Living, 2020)
Given the emergence of the COVID-19 outbreak, the official declaration of a global pandemic by the World Health Organization, and its consequential disruptions on the professional team sports landscape, it is the main objective of this brief opinion to help ensure that professional team-sport athletes and support staff remain aware as a society of some of the potential pitfalls – illustrated via negative but plausible detrimental scenarios. Finally, new ideas are introduced and evidence-based hypotheses are presented on the following five themes: periodization, exploration, virtual (at-home) training, player monitoring, and continued education, including return-to-competition preparation strategies following these exceptional times of uncharted territory.